Development of Business Platform Technology for Further Education in Modern University in the Tourism and Economic Forum Context - Anastasiya KOPYTOVA; Olga LOYKO; Valerii SIZOV; Olga SANFIROVA; Oksana NESTEROVA (Communications of International Proceedings, 2020)
The article considers the theoretical and methodological tools for the development of the business platform technology design for further education in a modern university in the context of the tourism and economic forum, which objective is to form the project skills of innovative brand project products, improving the skills of communicative interaction in an unconventional, artificially created market realities. The forum is defined as one of the educational technologies for the implementation of topic-centered interaction between educational entities in the format of a tourism and economic profile. The main components of the forum such as mission, main task, opportunity are described in the topic. The situation analysis is carried out, the project is presented, its main structural and thematic sections are indicated, and the technology for its implementation is described in detail. The main training profiles can be regional and international. Related types of educational tourism can be carried out within each module: linguistic, sports, communicational, business-oriented. The final part of the article contains the main business platform problem field, which includes the use of the following factors: cultural, psychological, and pedagogical. The article describes the forum thematic module in detail: “Market participants' brand communicative cooperation skills construction”. There are other modules topics, which can be the basis for any project content for the forum. Article presents the results of the forum elements approbation.
Keywords: Educational Process; Commercial Education; Development of Business Platform Technology; Forum Building Technologies; Forum Content.